Common and different doping patterns within photo-reactive complexes of Co2+ in Bi12SiO20 and Co3+ in Bi12TiO20 - YUMAK YAHŞİ, AYŞE (ELSEVIER GMBH, 2016)
In this work, impurity cross-section of Co doped Bi12MO20 (M = Si, Ti) is presented in the spectral region 1.5-2.25 eV. Einstein coefficients of both induced absorption, spontaneous and stimulated emission are determined as guides for the application of doped BSO and BTO in holography domains. Transition dipole moment and refractive index of Co doped crystals are calculated. The Lattice Compatibility Theory is also applied to the investigated samples. (C) 2016 Elsevier GmbH. All rights reserved.
Keywords: Optical materials and properties; Crystal structure; Defects; Microstructure; COMPATIBILITY THEORY LCT; OPTICAL-PROPERTIES; DOPED BI12SIO20; CATHODE MATERIALS; SINGLE; GROWTH; SPINEL; SILLENITES; LATTICES; BSO